The Influence of Brand Love, Trust and Brand Commitment on Word of Mouth on MS Glow Products - Octavia, Yusi Faizahtul; Hamdi, Nizar; Devi Puspaningrum, Ni Made Satya (Fakultas Agama Islam Universitas Islam Al-Azhar, 2024)
This study examines the effect of brand love, trust, and commitment on word-of-mouth for Ms Glow products among users of its Mataram branch. The independent variables were brand love, trust, and commitment while the dependent variable was word-of-mouth. The population was Ms Glow users in Mataram but the exact number is unknown. A purposive sample of 60 respondents was taken. Multiple linear regression analysis using SPSS 24 was conducted on the data. The results showed that brand love had a significant positive effect on word-of-mouth while trust and commitment did not. A simultaneous test found that the independent variables together influenced word-of-mouth. However, brand love had the strongest dominant influence on word-of-mouth for Ms Glow users based on its high t-count value. In summary, brand love drove word-of-mouth more than trust or commitment for this case study.